TRADITIONAL COCONUT OIL PURIFICATION USING ACTIVATED CHARCOAL COCONUT SHELL ADSORBENTS - Nining Putri Kurnianingsih; Maherwati Maherawati; Tri Rahayuni (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
Coconut oil in West Kalimantan is still largely a traditional coconut oil because it has not gone through a refining process. To improve the quality of traditional coconut oil, the addition of activated charcoal can be used as an adsorbent so as to improve the quality of coconut oil. Activated charcoal can be made from materials that contain high carbon, one of which is a coconut shell. The purpose of this study was to determine the effect of adding activated charcoal to improving the quality of traditional coconut oil and the concentration of adding activated charcoal that produced the best characteristics of coconut oil. The research design used was a Randomized Block Design with one factor (coconut shell active charcoal concentration) 6 levels of treatment (0%, 1%, 2%, 3%, 4%, 5%) with 4 replications. The data obtained were analyzed using ANOVA (ɑ = 5%) if there was an influence followed by BNJ test (ɑ = 5%). The results showed that the addition of coconut shell activated charcoal with a concentration of 1% -5% to traditional coconut oil can significantly reduce free fatty acid levels. In addition, the addition of activated charcoal affects the sensory attributes of color and aroma to be better than the control (without the addition of activated charcoal). The best traditional coconut oil produced in this study is traditional coconut oil added with coconut shell activated charcoal with a concentration of 5% with chemical and sensory characteristics as follows: water content 0.138%, free fatty acid content 0.428%, saponification number 231, 9 mg KOH / g, color value 4,88, and aroma value 3,68.Keywords: adsorbent, activated charcoal, coconut oil, refining, coconut shell